Development of a theory-based sexual and reproductive health promotion and HIV prevention program for Chinese early adolescents - Hong J. (2014)
The purpose of this study was to develop a theory-based program for Chinese early adolescents in order to promote their sexual and reproductive health and to prevent HIV infection. The program was designed based on the Information-Motivation-Behavioral skills model and a needs assessment among the stakeholders. A technical collaborative action research approach was applied. The study's participants were 102 early adolescents in a public middle school in mainland China, with the involvement of other key stakeholders, including 15 teachers and 12 parents. The results revealed a statistically significant improvement in the scores of sexual and reproductive health promotion and HIV prevention information, motivation, and behavioral skills after the program's implementation. Meanwhile, qualitative data from the early adolescents' reflection indicated that the content was useful and comprehensive, the trainers were friendly and knowledgeable, and participatory learning with an "edutainment" style was especially impressive. Additionally, the early adolescents expressed that they could apply the knowledge and skills in their daily life, which would benefit themselves and their family and peers. The Information-Motivation-Behavioral skills model could be explored in a non-Western context and the program was shown to be acceptable for use in a Chinese middle school setting. © 2010 Blackwell Publishing Asia Pty Ltd.